Splenic microanatomy of Scatophagus argus (Linnaeus, 1766) during juvenile stage - บุญยัง, ปิยากร; เสนารัตน์, ศิลปชัย; พูลประเสริฐ, พิสิษฐ์; จิรอังกูรสกุล, วรรณีย์; วังกุลางกูร, ศันสรียา (YRU Journal of Science and Technology, 2018)
The histological structure of the spleens in the juvenile Scatophagus argus was firstly investigated by using histology and histochemistry. Under the light microscopic level, the results revealed that the splenic parenchyma of this fish covered by a thin capsule which was a simple squamous epithelium, without the presentation of the trabeculae. Two main components consist of white and red pulps were distinctly seen in this organ. The white pulp shows slight basophilic staining with H&E and pinkish with PAS reaction. The blood vessel, erythrocyte and melamacrophage center were found. Whereas the red pulp contained of an ellipsoid and numerous cell types including erythrocytes, granulocyte and lymphocyte. Among their cells, the erythrocyte was the majority component in the splenic tissue of the S. argus juvenile.